A utilização de uma estratégia combinada de marketing experiencial e de influência para aumentar a notoriedade da marca : um estudo de caso - Sousa, Carolina Pinto de Andrade Almeida e (2019)
This paper aims to analyze, through a case study, if a combined strategy of experiential marketing and influence marketing can increase brand awareness and what are the factors involved in this approach. The investigation began with a literature review through the clarification of concepts such as experiential marketing, experience, influence marketing, word of mouth and brand awareness. The literature review was the basis to develop a study model to analyze the referred questions. To carry out the study we used a unique case study methodology following a descriptive approach, in which the brand under analysis was company X, client of Mojobrands agency. Several types of data were collected, including documents, articles, instagram posts, an interview with company X representative and pictures. This study concludes that a strategy combining experiential marketing and influential marketing, by generating greater engagement, more social media posts, and consequently more WOM, significantly amplifies brand awareness, promoting the brand within a substantially broader market.